Barriers and facilitators to implementation of nationwide electronic health records in the Russian Far East: A qualitative analysis. (November 2020) - Jung, Se Young; Lee, Keehyuck; Lee, Ho-Young; Hwang, Hee
Abstract: Background: Electronic health records (EHRs) are transforming and revolutionizing the healthcare industry. However, whereas developed countries have a high EHR penetration rate, adoption of EHRs in developing countries is lagging behind. Recently, the Korean and Russian governments have been pursuing economic cooperation in the Russian Far East. Thus, since 2009, Russia's EHR market and healthcare system have been maturing in tandem. Objective: To qualitatively investigate and analyze the current status of EHRs in the Russian Far East and derive implementation plans for nationwide EHRs. Methods: A qualitative analysis based on semi-structured interviews with healthcare professionals and administrative officers in the Russian Far East was conducted to illuminate the current status of EHRs and to collect various perspectives on barriers and facilitators to implementation. Results: The analysis revealed six major barriers and five major facilitators for implementation of nationwide EHRs in the Russian Far East. The barriers include lack of communications, an insufficient system development environment, poor adoption of standard terminology, poor infrastructure, resistance to a new system, and poor functionality. Facilitators include strategic government planning, centrally managed systems, health information exchange, willingness to use new functions, and well-established work processes. Conclusions: This study's results, along with the experiences of developed countries that have already successfully introduced EHRs, will help support successful introduction of EHRs in the Russian Far East.